Vinpocetine Inhibited the CpG Oligodeoxynucleotide-induced Immune Response in Plasmacytoid Dendritic Cells. (3rd April 2017) - Feng, Xungang; Wang, Yuzhong; Hao, Yanlei; Ma, Qun; Dai, Jun; Liang, Zhibo; Liu, Yantao; Li, Xiangyuan; Song, Yan; Si, Chuanping
ABSTRACT: Plasmacytoid dendritic cells (pDCs) exert dual roles in immune responses through inducing inflammation and maintaining immune tolerance. A switch of pDC phenotype from pro-inflammation to tolerance has therapeutic promise in the treatment of autoimmune diseases. Vinpocetine, a vasoactive vinca alkaloid extracted from the periwinkle plant, has recently emerged as an immunomodulatory agent. In this study, we evaluated the effect of vinpocetine on phenotype of pDCs isolated from C57BL/6 mice and explored its possible mechanism. Our data showed that vinpocetine significantly downregulated the expression of CD40, CD80, and CD86 on pDCs and increased the expression of translocator protein (TSPO), the specific receptor of vinpocetine, in pDCs. Vinpocetine significantly inhibited the Toll-like receptor 9 signaling pathway and reduced the secretion of related cytokines in pDCs through TSPO. Furthermore, viability of pDCs was significantly promoted by vinpocetine. These findings imply that vinpocetine serves as an immunomodulatory agent for pDCs and may be applied for the treatment of pDCs-related autoimmune diseases.